골반강 외에 발생한 자궁내막증식증 - 신현창(Hyeon Chang Shin); 정연준(Yeon Jun Jeong); 김종훈(Jong Hun Kim); 이민로(Min Ro Lee) (Annals of surgical treatment and research, 2006)
Purpose: Endometriosis is a condition where uterine mucosal tissue is located outside the uterus, and may be pelvic or extrapelvic. Extrapelvic endometriosis is a diagnostic challenge due to its very low incidence. The aim of this study was to analyze the clinical features of extrapelvic endometriosis in order to help diagnosis and treat this condition. Methods: Between January 1998 and May 2005, 6 patients diagnosed with extrapelvic endometriosis after surgery at our hospital were retrospectively reviewed by a telephone interview. Results: All cases were women in their reproductive years, with a median age of 37.5 years (range 34～50 years). Five of the six cases had a prior medical history of a caesarean section and 1 case had episiotomy during a normal vaginal delivery. Five cases were located in the lower abdomen and 1 case was located in the perineum. All patients presented with a surgical scar mass associated with pain and size that increased during menstruation. The median mass size was 2.5 cm (range 1～3.4 cm). The mass was found after a median interval of 13 months (range 1～45 months) from pelvic surgery. All cases were suspected of having extrapelvic endometriosis due to their specific clinical features, and 2 of them were confirmed by fine needle aspiration cytology (FNAC). All the patients were treated with a surgical excision. There was no recurrence after a median follow up of 27 months (range 4～86 months). Conclusion: Patients with a surgical scar mass associated with pain that increases in size during menstruation should be suspected of having extrapelvic endometriosis and be treated by a complete surgical excision to prevent a recurrence. (J Korean Surg Soc 2006;71:460-463) KCI Citation Count: 1